Synthesis and characterization of bimetallic nickel-cobalt chalcogenides (NiCoSe2, NiCo2S4, and NiCo2O4) for non-enzymatic hydrogen peroxide sensor and energy storage: Electrochemical properties dependence on the metal-to-chalcogen composition. (August 2019) - Sakthivel, Mani; Sukanya, Ramaraj; Chen, Shen-Ming; Pandi, Karuppiah; Ho, Kuo-Chuan
Abstract: To understand the application of transition metal based diselenide for electrochemical applications, NiCoSe2 is proposed as an excellent candidate with interesting physical and chemical properties. In this work, we have demonstrated the synthesis of NiCoSe2, NiCo2 S4, and NiCo2 O4 with different structures by using a simple hydrothermal method and further used as the electrode materials for electrochemical sensor and supercapacitor applications. For the first time, NiCoSe2 was used as a working electrode material to study the electrochemical sensing of hydrogen peroxide (H2 O2 ), and successively compared with the sensing response obtained at NiCo2 O4 and NiCo2 S4 modified electrodes. Especially, the detailed electrochemical kinetics of NiCo2 O4, NiCo2 S4, and NiCoSe2 electrodes were comparatively studied. The obtained results clearly indicate an excellent electrocatalytic activity of NiCoSe2 towards the electrochemical sensing of H2 O2 than that of NiCo2 O4 and NiCo2 S4 . The NiCoSe2 modified electrode exhibited an ultra-low detection limit (0.03 μM) and sensitivity (8.46 μA μM −1 cm −2 ) of H2 O2 . Additionally, we reported an excellent specific capacitance (1408.5 F g −1 ), higher specific surface area (94.81 m 2 /g) and lower charge transfer resistance (Rct = 0.13 Ω) of NiCoSe2 . Finally, we scrutinized that the NiCoSe2 is a promising electrode material for both electrochemical sensor and supercapacitor applications. Graphical abstract: Image 1 Highlights: The NiCoSe2, NiCo2 S4, and NiCo2 O4 were synthesized by using a hydrothermal method. NiCoSe2 /GCE was used as an efficient electrode for electrochemical sensing of H2 O2 . NiCoSe2 /GCE exhibited higher sensing response than that of NiCo2 O4 and NiCo2 S4 . The NiCoSe2 /GCE exhibited an ultra-low detection limit (0.03 μM) of H2 O2 . In addition, NiCoSe2 exhibited higher capacitance (1408.5 F g −1 ) at 1 A g −1 .